Malaysian English discourse particles and their meanings in Covid-19 themed YouTube videos - Tew, Jacqueline Hui Ee (2022)
This research aims to identify the types and placement of discourse particles in Malaysian YouTube videos and find out the meanings of the identified discourse particles. To date, there was a lack of research done on Malaysian English and its discourse particles, and no discourse particle study using YouTube videos as data which served as motivations for the current research. A corpus-based methodology was used to analyse seven COVID-19 themed YouTube videos made by Malaysian YouTubers collected between February 2020 and October 2021 with the addition of Tay et al. (2016)’s discourse particle categorisation as a framework. The research findings identified ten Malaysian English discourse particles and four discourse particles not listed in the framework or past studies. The findings showed that the framework could be updated as more content on Malaysian English discourse particles was shared throughout the media and people. Malaysia’s local languages were found to influence the creation of the identified discourse particles, especially the Chinese dialects and Malay language. Findings also showed that data from YouTube videos could provide accurate information on the uses of the discourse particles in daily utterances for future research. Likewise, this research proved Schneider’s Dynamic Model whereby Malaysian English is in the Nativisation phase because its linguistic features undergo structural nativisation.